Pengaruh Pemberian Ekstrak Cangkang Telur Bebek (Anas Plaptyrhynchos Domesticus) Konsentrasi 20% Dalam Sediaan Gel Dan Pasta Terhadap Kekerasan Permukaan Email Gigi Tikus Wistar (Rattus Norvegicus) : Studi (In Vivo) - Arvanita, Cindya; Agusmawanti, Prima; Niam, Husnun (Fakultas Kedokteran Gigi Universitas Jember, 2024)
Dental caries is a disease of the hard tissues of the teeth which is characterized by damage to the email and dentin caused by bacterial activity in fermented carbohydrates. One way to overcome and prevent caries is by giving anticariogenic substances that can inhibit caries development and trigger remineralization. As for other alternative materials used for remineralization, one of them is duck egg shell (Anas platyrhynchos domesticus) because it contains calcium carbonate which is in the eggshell can be converted into hydroxyapatite or calcium compounds, so that it can be used as the formation of damaged bones and teeth. In this study, duck egg shell hydroxyapatite extract was made in gel and paste preparations. In gel preparations, it has a high adhesive power so that the absorption on an email surface will be maximized. While in the preparation of pasta also has a great absorption power. This study aimed to determine the effect of hydroxyapatite gel and paste from duck eggshell extract (Anas platyrhynchos domesticus) and Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) on the tooth email hardness of wistar rats (Rattus norvegicus). In this study there were 3 treatment groups. Prior to treatment, the tooth sample was etched in the labial section for 20 seconds and rinsed using a brush and water. After etching was applied, in group 1, duck egg shell hydroxyapatite extract gel was applied, in group 2, duck egg shell hydroxyapatite extract paste was applied, and in group 3 as a control group, CPP-ACP was applied to the lower anterior teeth of wistar rats for 30 minutes 2 times a day. for 14 days. On the 15th day, the lower anterior teeth were decapitated by wistar rats and hardness testing was carried out using microvikers hardness in the labial part of the teeth. This research is a true experimental with Post Test Control Group Design. The result of the average hardness of email that has been treated with the highest hardness is CPP-ACP of 332 VHN. The results of the normality test using Shapiro Wilk showed that the duck egg shell extract gel could increase the surface hardness of tooth email. The results of the comparison test using Kruskal Wallis showed that there was a change in hardness between the hydroxyapatite gel of duck eggshell extract, hydroxyapatite paste of duck eggshell extract and CPP-ACP and there were significant differences. From the results of this study, there was an increase in the surface hardness of tooth email after the application of duck egg shell hydroxyapatite gel (Anas platyrhynchos domesticus) compared to paste preparations and as a positive control with CPP-ACP also increased the hardness of tooth email.